2022
DOI: 10.1371/journal.pone.0262437
|View full text |Cite
|
Sign up to set email alerts
|

Independent effect of gestational weight gain and prepregnancy obesity on pregnancy outcomes among Saudi women: A sub-cohort analysis from Riyadh mother and baby cohort study (RAHMA)

Abstract: Background Gestational weight gain (GWG) and prepregnancy obesity are garnering more attention as determining factors of pregnancy outcomes when it comes to the wellbeing of both the mother and her baby. This study was conducted to describe the pattern of GWG among participants of Riyadh Mother and Baby Multicenter Cohort Study (RAHMA) and to investigate the detrimental effects of excessive GWG and prepregnancy obesity on pregnancy outcomes. Methods RAHMA is a multicentre cohort study conducted in three hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
3
9
1
1
Order By: Relevance
“…The frequency of pregnancy, which was accompanied by gestational and pregestational diabetopathy was 4.3% in our study, which coincided with the data of previous studies (Fayed A et al, 2022). Diabetes mellitus significantly more often accompanied macrosomal pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of pregnancy, which was accompanied by gestational and pregestational diabetopathy was 4.3% in our study, which coincided with the data of previous studies (Fayed A et al, 2022). Diabetes mellitus significantly more often accompanied macrosomal pregnancies.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, studies have found that the incidence of excessive GWG is as high as 50% in reproductive-age women and in pregnant women [ 3 , 4 ], and about one-quarter (25.6%) of the population is obese before pregnancy [ 5 ]. Maternal obesity before pregnancy or excessive GWG during pregnancy can lead to a variety of adverse pregnancy outcomes, such as hypertensive events, gestational diabetes, emergency cesarean section and macrosomia [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IOM guidelines recommend the following cut-off values for adequate GWG: a total weight gain of 12.5-18 Kg for underweight BMI women (≤18.5 kg/m²), a total weight gain of 11.5-16 kg for normal BMI women (18.5-24.9 kg/m²) , a total weight gain of 7-11.5 kg for overweight women (BMI of 25-29.9 kg/m²) , a total weight gain of 5-9 kg for all obese women (BMI of 30 kg/m² or greater) (Fayed et al, 2022). (Anita & Weeks, 2018) are reflecting upon GWG, it is crucial to recognize that discordant GWG is both an independent and a modifiable risk factor for many pregnancy complications (Chamara et al, 2019).…”
Section: Unsatisfactorymentioning
confidence: 99%